Pengaruh Dukungan Manajemen Puncak, Pemanfaatan Teknologi Informasi Dan Pengalaman Kerja Terhadap Efektivitas Sistem Informasi Akuntansi - Ivi Novianti; Khamimah Khamimah (Universitas 17 Agustus 1945, 2023)
This study aims to determine the effect of top management support (X1), utilization of information technology (X2) and work experience (X3) on the effectiveness of accounting information systems (Y). The population used in this study were 47 KSPPS BMT Bina Ummat Sejahtera employees in the Semarang area. The sampling method used is saturated sample (census). The data in this study are primary data obtained from distributing questionnaires to KSPPS BMT Bina Ummat Sejahtera Semarang Region employees. The data analysis technique used multiple linear regression analysis with the help of SPSS 21 software. The results showed that top management support (X1), utilization of information technology (X2) and work experience (X3) were significant for increasing the effectiveness of accounting information systems (Y).